FRI0227 Five-Year Safety and Efficacy of Subcutaneous Abatacept in Patients with Moderate To Severely Active RA and An Inadequate Response To MTX: Long-Term Extension of The Phase III, Double-Blind, Randomized Acquire Study. (15th July 2016) - Genovese, M.C.; Pacheco Tena, C.; Covarrubias, A.; Leon, G.; Mysler, E.; Keiserman, M.; Valente, R.; Nash, P.; Simon-Campos, J.A.; Box, J.; Legerton, C.W.; Nasonov, E.; et al.
Abstract : Background: The ACQUIRE study demonstrated non-inferiority of the SC to the IV formulation. 1 Objectives: To assess the 5-yr safety and efficacy of SC ABA 125 mg/wk plus background MTX in the LT extension (LTE). Methods: The 6-month, double-blind (DB) period was followed by an open-label LTE in which patients (pts) received SC ABA 125 mg/wk. Dose adjustments to MTX, corticosteroids and NSAIDs were permitted. Safety, efficacy and immunogenicity assessments were performed at 12-wk intervals. Safety and efficacy analyses included all pts who entered the LTE and received ≥1 dose of ABA. Results: 1373/1385 pts who completed the DB period entered the LTE, 427 (31.1%) had discontinued by end of Yr 5 (due to AE: 100 [7.3%]; lack of efficacy: 89 [6.5%]; withdrawal of consent: 81 [5.9%]). In the LTE, 1240 pts (90.3%) had an AE (Table), most (79.8%) were mild/moderate; most frequent non-serious AEs were infections. Overall, 353 pts (25.7%) had an SAE. The incidence rate/100 pt-yrs (95% CI) for SAEs decreased from 9.02 (6.31, 12.90) in the DB period to 7.73 (6.96, 8.58) during the LTE (332.6 and 4566.2 pt-yrs of exposure, respectively). Efficacy in the LTE was consistent with the DB phase and was maintained to 5 yrs in pts who remained on study: at Day 1821, 356/421 (84.6%), 277/423 (65.5%) and 191/425 (44.9%) had an ACR20, 50 or 70 response, respectively. ABA trough concentrations were stable over the LTE. Immunogenicity was low over 5 yrs (4.6/100 pt-yrs); there was no association between immunogenicity and ABA efficacy, safety or PK. Conclusions: During this 5-yr LTE of the ACQUIRE study, the safety and efficacy of SC abatacept were consistent with that seen in the initial DB phase, with no new safety signals. References: Genovese M, et al. Arthritis Rheum 2011;63:2854–64. Disclosure of Interest: M. C. Genovese Grant/research support from: Bristol-Myers Squibb, C. Pacheco Tena Grant/research support from: UCB, Speakers bureau: Bristol-Myers Squibb, Roche, AbbVie, UCB, Janssen, A. Covarrubias: None declared, G. Leon: None declared, E. Mysler Grant/research support from: Bristol-Myers Squibb, Roche, Speakers bureau: Bristol-Myers Squibb, Roche, M. Keiserman Grant/research support from: AbbVie, Actelion, Anthera, Biogen, Bristol-Myers Squibb, Celltrion, Eli Lilly, HGS, Janssen, Novartis, Pfizer, Roche, Sanofi, UCB Pharma, Speakers bureau: AbbVie, Janssen, R. Valente Grant/research support from: Novartis, Bristol-Myers Squibb, Pfizer, Takeda, Sanofi, Lilly, Boehringer Ingelheim, AbbVie, AstraZeneca, Sandoz, P. Nash: None declared, J. A. Simon-Campos: None declared, J. Box: None declared, C. W. Legerton III Grant/research support from: AbbVie, Ablynx, Acerta, Amgen, AstraZeneca, Celgene, GSK, Janssen, Eli Lilly, Bristol-Myers Squibb, Pfizer, Novarits, Sandoz, UCB, Daiichi Sankyo, ChemoCentryx, Boehringer Ingelheim, Speakers bureau: Celgene, Amgen, E. Nasonov: None declared, P. Durez Speakers bureau: Bristol-Myers Squibb, Samsung, Pfizer, UCB, Mundipharma, Hospira, Lilly, A. Elegbe Shareholder of: Bristol-Myers Squibb, Employee of: Bristol-Myers Squibb, R. Wong Shareholder of: Bristol-Myers Squibb, Employee of: Bristol-Myers Squibb, X. Li Shareholder of: Bristol-Myers Squibb, Employee of: Bristol-Myers Squibb, S. Banerjee Shareholder of: Bristol-Myers Squibb, Employee of: Bristol-Myers Squibb, R. Alten Grant/research support from: Bristol-Myers Squibb, Consultant for: Bristol-Myers Squibb, Speakers bureau: Bristol-Myers Squibb